Assessing awareness and utilisation of pre-exposure prophylaxis for HIV prevention among women who inject drugs in Lagos, Nigeria: a cross-sectional study - Olanrewaju Onigbogi; Modupe Onigbogi; Osadebamwen N Eghaghe; Omobola Y Ojo; Oluwatoyin Funmilola Babalola (BMJ Public Health, 2024)
Introduction Women who inject drugs (WWID) in Nigeria are more likely to be living with HIV than their male counterparts and could benefit from pre-exposure prophylaxis (PrEP). Our study therefore sought to determine the awareness and use of PrEP among WWID in Lagos, Nigeria.Methods The study was descriptive cross-sectional in design and involved 422 participants recruited by using the snowballing technique. Interviewer-administered questionnaires were used to collect data which were analysed using Epi Info software and presented as frequency tables. χ2 test was used to analyse the categorical data and investigate relationships, associations, and independence between categorical variables with the level of significance set at p<0.05.Results There were 422 respondents with 60.2% of them between 18 and 30 years of age with the majority (90.1%) identifying as females while 6.9% identified as transgender. Half of the respondents (50.2%) were unemployed, 56.6% were single while 7.8% were aware of PrEP with only 1.9% reporting that they had ever used it. Factors significantly associated with awareness of PrEP were age (p<0.038), period of residence (p<0.001) and the level of education (p<0.001). Increased awareness of PrEP was associated with residence within the local government area for 1 year or more (adjusted OR (AOR) 0.20, 95% CI 0.08 to 0.49) and completion of at least secondary school education (AOR 7.63, 95% CI 2.59 to 22.45).Conclusions This study sheds light on the crucial issue of awareness and utilisation of PrEP for HIV prevention among WWID in Lagos, Nigeria. The findings highlight the need for tailored interventions bearing in mind the determinants of PrEP use within this specific demographic group. Addressing these correlates of PrEP use will be pivotal in developing effective strategies to reduce HIV transmission and improve the overall health outcomes in this vulnerable population.